Exploring an Islamic student housing framework in Semarang, Indonesia / Muhammad Ismail Hasan - Muhammad Ismail , Hasan (2024)
This study aims to reveal the Islamic value of Islamic Student Housing (ISH) in Semarang, Indonesia. This study investigates how Islamic university students dwelling in student housing conduct their daily activities. The goal is to develop a design framework for creating ISH design that include Islamic values. This study utilized constructivism grounded theory with a FGD and observation method. The collected data is then visualized to create a spatial representation of space use. According to the findings of this study, three factors must be considered while creating user-based ISH: privacy, sociability and orientation. These three aspects allow for an ISH design that prioritizes typology while putting the user first. Furthermore, the study's findings point to the presence of an ISH spatial planning system that takes into account both external and internal relationships. Spatial configurations that considering the interaction between space and interior have the potential to create an ISH space system based on Islamic values.